2020
DOI: 10.1074/jbc.ac120.016191
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping function of Hrd1 and Ste24 in translocon quality control provides robust channel surveillance

Abstract: Translocation of proteins across biological membranes is essential for life. Proteins that clog the endoplasmic reticulum (ER) translocon prevent the movement of other proteins into the ER. Eukaryotes have multiple translocon quality control (TQC) mechanisms to detect and destroy proteins that persistently engage the translocon. TQC mechanisms have been defined using a limited panel of substrates that aberrantly occupy the channel. The extent of substrate overlap among TQC pathways is unknown. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…We favor the hypothesis that ZMPSTE24's other crucial cellular functions, in addition to prelamin A cleavage, contribute to the severity of phenotypes and limited lifespan of the Zmpste24 -/mice. ZMPSTE24 has a key role in clearing clogged translocons, as well as other less mechanistically well understood roles in viral defense, protein secretion, ER protein quality control, membrane stress, and establishing membrane protein topology (14)(15)(16)(17)(18)(19)(20)(21)(22). Loss of one or several of these other functions may make Zmpste24 -/mice more susceptible to the "toxic" effects of prelamin A or create additional pathologies that exacerbate those resulting from prelamin A. Lmna L648R/L648R mice also live significantly longer and have milder phenotypes than reported for various mouse models expressing progerin, the prelamin A variant in HGPS (26-29, 31, 37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We favor the hypothesis that ZMPSTE24's other crucial cellular functions, in addition to prelamin A cleavage, contribute to the severity of phenotypes and limited lifespan of the Zmpste24 -/mice. ZMPSTE24 has a key role in clearing clogged translocons, as well as other less mechanistically well understood roles in viral defense, protein secretion, ER protein quality control, membrane stress, and establishing membrane protein topology (14)(15)(16)(17)(18)(19)(20)(21)(22). Loss of one or several of these other functions may make Zmpste24 -/mice more susceptible to the "toxic" effects of prelamin A or create additional pathologies that exacerbate those resulting from prelamin A. Lmna L648R/L648R mice also live significantly longer and have milder phenotypes than reported for various mouse models expressing progerin, the prelamin A variant in HGPS (26-29, 31, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, some of the organismal pathology caused by ZMPSTE24 deficiency may result from defects in protein translocation into the endoplasmic reticulum (ER). ZMPSTE24 may also have additional functions, inferred from its contribution to viral defense in mice (16,17) and from genetic studies in yeast that have implicated it in ER protein quality control, membrane stress, and establishing membrane protein topology (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work in yeast identified the protease, Ste24, as the de-clogger of the Sec61 translocon [ 1 ]. New evidence indicates that Ste24 and a central component of yeast ERAD, Hrd1 [ 28 ], act redundantly to promote degradation of aberrant proteins that stably associate with the translocon. Hrd1 can also compensate for loss of Dfm1, another core ERAD component that is required for the extraction of membrane-embedded substrates [ 20 , 21 ].…”
Section: Destruction Of Aberrant Membrane Proteinsmentioning
confidence: 99%
“…A conceivable distinction between different TAQC substrates may lie in the state of translocon clogging. Transient clogging due to suboptimal signal sequence may result in the recruitment of ER chaperons to resolve clogged translocon while keeping the nascent chains in the biosynthetic path ( Sha Sun, 2020 ), but aberrant translocon engagement for substrates with either a translocation-impeding domain or deregulated lipid binding (e.g., apoB) may reverse the translocation process, causing the degradation of aberrant polypeptides in the cytosol ( Hrizo et al, 2007 ; Rubenstein et al, 2012 ; Runnebohm et al, 2020 ). By contrast, permanent stalling by translation arrest might lock the translocation process in an irreversible state, prompting the release of the stalled polypeptides only toward the ER lumen for clearance by other mechanisms (see below).…”
Section: Translocon Declogging During Cotranslational Translocationmentioning
confidence: 99%
“…They found that the folding of this substrate prior to ER translocation causes translocon clogging, resulting in the recruitment of Ste24 (ZMPSTE24 in mammals) to the clogged translocon and subsequent cleavage of the partially translocated polypeptide by the metalloprotease activity of Ste24 (Ast et al, 2016). Besides Ste24, a recent study demonstrated a role for Hrd1 in degradation of this model substrate, probably via an ERAD-like or the aforementioned ER-pQC mechanism (Runnebohm et al, 2020). These mechanisms may collectively resolve clogged translocons to maintain the secretory homeostasis (Figure 2A).…”
Section: Translocon Declogging During Posttranslational Translocationmentioning
confidence: 99%